STUDI PENDAHULUAN: KONSTRUKSI INSTRUMEN PENILAIAN ANALISIS KONTEN BUKU TEKS GEOGRAFI BERBASIS NILAI PPK - Rafika Hasanah; Ernawati Ernawati (Universitas Negeri Gorontalo, 2020)
Geography is one of the lessons that support character education and integrate it into textbooks. An assessment instrument is needed to determine the value of PPK (Strengthening Character Education) in the textbook. This study aims to design an instrument for evaluating PPK values in textbooks with indicators of nationalism and mutual cooperation. This research uses a quantitative descriptive method in the form of a questionnaire and is integrated with natural disaster mitigation materials. The results showed 1 indicator with no PPK values, 11 indicators with no PPK values, and 7 indicators with PPK values. The trials of this instrument need to be broadly developed to obtain perfect instrument validity.